An IoT platform for seizure alert wearable device - Emelia Akashah, P.A. (Institute of Physics Publishing, 2020)
This research aims to propose the system architecture for a wearable device that is able to detect seizure attacks for children aged 15 years old and below. The objective of this research is to alert parents or relatives of the patients whenever the seizure attack is detected. In many cases, seizure attack happened in absences of the parents or relatives. Therefore, the wearable device proposed in this research should be able to monitor their children heart rate and motion remotely. Notification also will be sent to parents or relatives via mobile apps should there is any trigger of seizure detection. Data were collected via interview. The IoT wearable device architecture was then designed before being implemented. Â© Published under licence by IOP Publishing Ltd.